Development of Disaster Knowledge Measurement Instrument for Visitors in Volcanic Tourism Areas - Budiatiningsih, Mahmudah; Ikhsanudin, Ikhsanudin; Irsyad, Maulana Malik (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2025)
This study aims to develop an instrument to measure the disaster knowledge of the visitors of volcanic disaster-prone tourism area. This study is a design and development research, using test development procedure stated by Oriondo & Dallo-Antonio. The test development procedures are (1) designing or drafting test, (2) field testing, (3) measuring validity, (4) measuring reliability. The field test was done by online test on 123 respondents that were sampled by convenience sampling. The test instrument analysis was done by expert judgement, the objective validity test based on Rasch Model and the reliability test based on K-20 reliability test. The objective validity and reliability test were done using Quest program. The test results showed that the instruments are valid and reliable. The objective validity test showed that 31 items on the instruments fit with Rasch model with the items range of INVIT MNSQ score are 0.88-1.11 and the items range of OUTFIT T are -1 to +1.2. The item reliability score is 0.96 and the case reliability score is 0.59. Based on the validity and reliability tests results, the instrument is qualified to measure the volcanic disaster-prone tourism area visitors’ disaster knowledge.